Chiral induction in a pcu-derived network from achiral precursors12. Issue 32 (8th March 2019) - Xue, Hui; Zhou, Kang; Liu, Luyao; Wu, Dong; Hong, Zixiao; Chen, Qihui; Jiang, Feilong; Yuan, Daqiang; Zhang, Jian; Hong, Maochun
Abstract : The first chiral network derived from a classicpcu net has been rationally prepared from achiral precursors. Abstract : Rational induction of chirality from achiral systems is one of the most compelling challenges for chemists. Herein, the first chiral net derived frompcu topology has been prepared using the vertex splitting and ligand anchoring strategy, showing a new way to construct chiral frameworks from achiral precursors.